Experienced-based Instruction of Writing Skill to Iranian Intermediate EFL Learners - Pourhosein Gilakjani, Abbas (International Journal of Education and Cognitive Sciences, 2026)
Purpose: The current study examines the effectiveness of the EI model in improving Iranian intermediate EFL learners’ writing ability.Methodology: The research method was quasi-experimental with a pretest-treatment-posttest design. To this end, forty-eight learners, taking English course at Shokooh English Language Institute, in Rasht, Iran, were selected as intermediate homogeneous participants based on Solutions Placement Test. Next, they were assigned to one experimental and one control group. During the treatment that lasted for 12 sessions, the researchers applied pre-teaching activities and teaching activities including observing, questioning, exploring/experimenting, associating, and communicating for the experimental group, which was followed by asking them to do some reflection on their work and think how they experienced the participation. In the control group, however, was exposed to conventional mainstream of teaching writing. The respective post-test results analyzed based on independent and paired samples t-tests.Findings: The findings revealed that EI had statistically significant effect on the learners’ writing ability. So the EI model is suggested over the common teaching methods of writing skill but the generalizability of the results to other skills has to wait for further research.Conclusion: According to the results of this study, the role of the EI model in improving writing skill has important pedagogical implications.